Characterization of Thermally Oxidized Ti6Al4V Alloys for Dental Application - A. Boucheham; A. Karaali; B. Rahal; Y. Belkacem (Журнал нано- та електронної фізики)
In this work, thermal oxidation processes in the temperature range of 500-800 °C in air for 4 hours were performed on Ti6Al4V medical grade alloys to modify their surface structure and morphology for better wear and corrosion resistance, osseointegration and biocompatibility. Different type and amount of nanostructured phases were obtained as revealed by the X-ray diffration (XRD) technique such as: alumina, anatase and rutile. X’pert high score plus software was used for the calculation of the percentage and crystallite sizes of these phases. Alumina phase exhibits the greater amount of the oxide layers when Ti6Al4V alloys annealed at 500 °C, while rutile was found to be the predominant phase at 800 °C.